Production and Characterisation of Lignin Peroxidase from Newly Isolated Thermophilic Bacillus licheniformis from Empty Fruit Bunch - Lai, Carol Mei Teng (Curtin University, 2023)
This research was initiated to screen for thermophilic ligninolytic bacteria native to Empty Fruit Bunch (EFB) compost with the aim of isolating and identifying bacteria with lignin degrading activity and carrying out a more in-depth study and evaluation on the production and characterisation of the key lignin degrading enzymes, namely lignin peroxidase, LiP from a newly isolated ligninolytic bacterium, Bacillus licheniformis.